2018
DOI: 10.1088/2058-6272/aab5bc
|View full text |Cite
|
Sign up to set email alerts
|

Gyrokinetic theory of turbulent acceleration and momentum conservation in tokamak plasmas

Abstract: Understanding the generation of intrinsic rotation in tokamak plasmas is crucial for future fusion reactors such as ITER. We proposed a new mechanism named turbulent acceleration for the origin of the intrinsic parallel rotation based on gyrokinetic theory. The turbulent acceleration acts as a local source or sink of parallel rotation, i.e., volume force, which is different from the divergence of residual stress, i.e., surface force. However, the order of magnitude of turbulent acceleration can be comparable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The argument was made [56,57,58,59] that in experimental measurements the parallel velocity u ∥ is measured and not the parallel momentum density nu ∥ . It was concluded that therefore u ∥ respectively ⟨u ∥ ⟩ should be the quantity that theoretical work should focus on when discussing intrinsic rotation.…”
Section: Comparison To Parallel Accelerationmentioning
confidence: 99%
See 2 more Smart Citations
“…The argument was made [56,57,58,59] that in experimental measurements the parallel velocity u ∥ is measured and not the parallel momentum density nu ∥ . It was concluded that therefore u ∥ respectively ⟨u ∥ ⟩ should be the quantity that theoretical work should focus on when discussing intrinsic rotation.…”
Section: Comparison To Parallel Accelerationmentioning
confidence: 99%
“…Also, recall that even though it is not technically wrong to compute ⟨u ∥ ⟩ the fluxsurface average (7) is a volume average and should be taken over density like quantities (like nu ∥ ). Finally, what comes out of a gyro-kinetic moment expansion (as performed in [56,57,58,59]) is the gyro-fluid parallel velocity U ∥ , not the actually measured fluid velocity u ∥ . As we discuss in Sec.…”
Section: Comparison To Parallel Accelerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, ∥ is the parallel current density, In this work, we focus on the intrinsic current drive which is independent of the mean parallel current density or its gradient. This is analogous to the intrinsic rotation drive by the residual stress, kinetic stress, and turbulent source [26][27][28].…”
Section: Quasi-linear Estimate For Intrinsic Parallel Current Densitymentioning
confidence: 99%
“…The topic of an exact gyrokinetic momentum conservation law gained crucial importance in the context of the momentum transport (Waltz et al 2007; Parra & Catto 2010 a ; Abiteboul et al 2011; Peeters et al 2011) and intrinsic toroidal rotation (Wang, Peng & Diamond 2018; Stoltzfus-Dueck 2019) in axisymmetric tokamak plasmas. In particular, the phenomenon of intrinsic toroidal rotation, which is observed in the absence of external torque, must be investigated within the context of toroidal angular momentum conservation.…”
Section: Introductionmentioning
confidence: 99%